KUAT TARIK BELAH DAN LENTUR BETON DENGAN PENAMBAHAN STYROFOAM (STYROCON) - Dharma Giri, I.B.; Sudarsana, I Ketut; Agustiningsih, N.L.P. Eka (Jurnal Ilmiah Teknik Sipil; Vol. 12, No. 2 Juli 2008)
Application of lightweight material as former structure will reduce total weight of a building. Lightweight concrete is one of the lightweight structural former materials. In making of lightweight concrete, one of alternative material that used is styrofoam. Styrofoam generally used as materials that covering electronic things. Styrofoam use in lightweight concrete can be as air voids. The advantages of styrofoam than air void in lightweight concrete are that styrofoam have tensile strength. According to those, the aims of this research were to obtain the influence of adding styrofoam to volume of weight, splitting tension and modulus of rupture. The specimens for splitting test were cylinders with dimension of 150 mm in diameter and 300 mm in height and specimens for modulus of rupture were beam with dimension of 150 x 150 x 600 mm. Seven specimens were used for splitting test and 3 for modulus rupture test for any variation of percentage increased of styrofoam. Concrete was made by weight comparison of 1 : 2 : 3. The amount of cement in 1 m3 concrete mixture was 400 kg. Variation of percentage increased styrofoam were 0%, 10%, 20%, 30%, 40% to volume of mixture. The range diameter granular styrofoam are 3 – 10 mm with volume of weight of 22,89 kg/m3. Slump test is done to fresh concrete, volume of weight measurement, splitting and modulus rupture test were done after 28 days. Result showed that increased of styrofoam increased the slump value. Volume of weight and splitting tension decreased linearly. The adding of 10% granular styrofoam decreased the volume of weight and splitting tension by 81,08 kg/m3 (4,01%) and 0,34 MPa (12,19%), respectively. The change of modulus rupture value at 10% adding of styrofoam was 22,67% and at 20% adding of styrofoam was 29,62% to concrete without adding of Styrofoam. However at 30% adding of Styrofoam, modulus rupture increased by 1,21% to concrete with 20% adding of styrofoam.
Keywords: beton ringan, styrofoam, berat satuan, kuat tarik belah, kuat tarik lentur